145k views
4 votes
(×-5) second power equals 3​

User Jbrown
by
5.5k points

1 Answer

6 votes

Answer:
x_1=6.73\\\\x_2=3.26

Step-by-step explanation:

Given the following expression:


(x-5)^2=3

And knowing that:


(a\±b)^2=a^2-2ab+b^2

We get:


x^2-2(x)(5)+5^2=3\\\\x^2-10x+25=3

Move the 3 to the left side of the equation:


x^2-10x+25-3=0\\\\x^2-10x+22=0

Apply the Quadratic formula:


x=(-b\±√(b^2-4ac) )/(2a)

In this case:


a=1\\b=-10\\c=22

Substituting values into the Quadratic formula, we get:


x=(-(-10)\±√((-10)^2-4(1)(22)) )/(2(1))\\\\\\x_1=6.73\\\\x_2=3.26

User Dima Bildin
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.